Income Risk of German Farms and its Drivers - Christoph Duden; Frank Offermann (German Journal of Agricultural Economics (GJAE), 2020)
The analysis of income risk is the basis for successful whole farm risk management. The measurement of risks helps to objectively assess the farms' individual risk exposure. However, due to limited data availability, comprehensive overall risk analyses are often scarce, e.g. for Germany. The present study analyses risk exposure for more than 3,000 farms in Germany in the period 1996/97-2015/16 on the basis of the national Farm Accountancy Data Network (FADN). Our results show that (i) risk exposure is heterogeneous and that fluctuations and particularly large decreases in farm income are rarely attributable to individual risk components (e. g. prices or yields), (ii) farm income risk has been higher in the period after 2007 for many farms, especially arable and dairy farms, (iii) while the income risk in dairy farming increased, it is still lower than that of most other farm types in the period 2006/07-2015/16, (iv) the for-mation of expected values has a significant influence on the absolute level of the measured risk and should be given more attention in future research.
Keywords: 330